The Ruling for Circumambulation on the Upper Floors of Kaâba - Ã˜Â¹Ã™Â†Ã˜Â§Ã›ÂŒÃ˜ÂªÃ›ÂŒ Ã˜Â±Ã˜Â§Ã˜Â¯, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯ Ã˜Â¬Ã™ÂˆÃ˜Â§Ã˜Â¯ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Circumambulation literary means turning around something paralleled with sensual and spiritual surrounding. The soundness of circumambulating on the floors higher than the Kaâba is relied on the conventional verity of circumambulation and relevance of the location of the House to the traditions and annexation of the air of the Mosque and Kaâba to the Mosque and Kaâba. Besides being weak in chain of transmission, the traditions relied on have no fully approved evidentiary proof either; and the verse ï´¾and go about the Ancient Houseï´¿ (Q. 22: 29) and the traditions of circumambulation of the House in conjunction with non-lenient conventional understanding appear to take the House itself as a pivot for circumambulation.